Routine induction in late-term pregnancies: follow-up of a Danish induction of labour paradigm - Eva Rydahl; Eugene Declercq; Mette Juhl; Rikke Damkjær Maimburg (BMJ Open)
Objectives For many years, routine elective induction of labour at gestational week (GW) 42+0 has been recommended in Denmark. In 2011, a more proactive protocol was introduced aimed at reducing stillbirths, and practice changed into earlier routine induction, i.e. between 41+3 and 41+5 GW. The present study evaluates a national change in induction of labour regime. The trend of maternal and neonatal consequences are monitored in the preintervention period (2000–2010) compared with the postintervention period (2012–2016).Design A national retrospective register-based cohort study.Setting Denmark.Participants All births in Denmark 41+3 to 45+0 GWs between 2000 and 2016 (N = 152 887).Outcome measures Primary outcomes: stillbirths, perinatal death, and low Apgar scores. Additional outcomes: birth interventions and maternal outcomes.Results For the primary outcomes, no differences in stillbirths, perinatal death, and low Apgar scores were found comparing the preintervention and postintervention period. Of additional outcomes, the trend changed significantly postintervention concerning use of augmentation of labour, epidural analgesia, induction of labour and uterine rupture (all p<0.05). There was no significant change in the trend for caesarean section and instrumental birth. Most notable for clinical practice was the increase in induction of labour from 41% to 65% (p<0.01) at 41+3 weeks during 2011 as well as the rare occurrence of uterine ruptures (from 2.6 to 4.2 per thousand, p<0.02).Conclusions Evaluation of a more proactive regimen recommending induction of labour from GW 41+3 compared with 42+0 using national register data found no differences in neonatal outcomes including stillbirth. The number of women with induced labour increased significantly.